A Study on the Use of Copper Ions for Bacterial Inactivation in Water - Teksoy, Arzu; Ozyigit, Melis Ece (Mdpi, 2025)
This study comprehensively evaluated the antimicrobial performance of copper ions against three bacterial species relevant to water systems: E. coli (ATCC 25922), P. aeruginosa (ATCC 27853), and S. epidermidis (ATCC 12228). Disinfection kinetics were determined at three copper concentrations (0.5, 1.5, and 3.3 mg/L) using the Gard model. E. coli exhibited the highest susceptibility, with inactivation rate constants of 0.63, 3.27, and 9.83, achieving complete inactivation at 3.3 mg/L. P. aeruginosa was the most resistant, showing values below 1.0 across all concentrations, while S. epidermidis displayed intermediate responses. Selected experiments further examined the influence of growth phase, temperature, and water chemistry. Exponential-phase cells were more sensitive than stationary-phase cultures, and higher temperatures (37 degrees C vs. 5 degrees C) significantly enhanced inactivation. Moderate bicarbonate (50 mg/L) improved bacterial removal by stabilizing soluble Cu2+ ions (2.60 lg reduction), whereas elevated calcium and magnesium (Ca2+ 100 mg/L, Mg2+ 50 mg/L) reduced effectiveness (<= 2.10 lg reduction) through competitive interactions. In addition to culture-based methods, adenosine triphosphate (ATP) bioluminescence assays and flow cytometry (FCM) provided complementary insights, confirming early metabolic disruption and membrane damage prior to culturability loss in selected experiments.
Keywords: copper ionization; bacterial inactivation; E. coli; P. aeruginosa; S. epidermidis; water disinfection